FORMATION OF INVESTMENT STRATEGY IN FINANCIAL INDUSTRIAL GROUPS USING SYSTEM ANALYSIS - Slushaienko, Nataliia (Ekonomika, 2012)
Abstract. In the article, the author investigates the definition of the investment strategy that will bring the maximum effect, which is the main objective of target coordination. The proposed model takes into accountthe factors of investment projects that are particularly important for financial and industrial groups, for evaluating investment projects and the impact of individual elements on other units.Key words: investment projects, economic efficiency, economic and mathematical models, comparison criteria, portfolio investments